Slope Stability Monitoring Using GSM Network System - R.C. Omar; H. Taha; N.H.N Khalid; R. Roslan; I.N.Z. Baharuddin; F. Ahmad (International Association of Lowland Technology, 2020)
Slope failure due to slope instability can initiate landslides whichmay result in loss of lives, property, infrastructures and economicloss. There are many factors that trigger slope failure such asrainfall, hydrological condition, groundwater level and geologicalformation of the slope area. However, slope failures can beprevented by monitoring high risk slopes using geotechnicalinstruments and electronic sensors. In this study, an early warningsystem was developed to immediately alert the authority and themanagement on slope stability by installing selected slopemonitoring instruments at high risk slopes with infrastructures.Slope monitoring system using wireless network is an effectivemethod to monitor the condition of slopes especially theinaccessible slopes in unsafe areas. By applying this system, themanagement can reduce cost, human resources and time onslope maintenance that can efficiently notify themaintenance team on potential unsafe slopes or slope failures